Penyuluhan penanganan panen dan pasca panen padi gogo di Desa Pollewani, Kecamatan Tubbi Taramanu, Polewali Mandar - Syah, Ikrar Taruna; HM., Rahmaniah; Utami, Rahmawati Ning (Jurnal Tarreang: Tren Pengabdian Masyarakat Agrokompleks, 2025)
Polewali Mandar Regency comprises 16 sub-districts, with the most significant administrative area being Tubbi Taramanu Sub-district, which is one reason this region remains less "touched" by the local government. One of the main agricultural products of the residents of Tubbi Taramanu Sub-district is upland rice with a yield of 3.97 tons.ha–1 in 2023. However, this yield, compared with other major food crops, is still much lower than that of cassava, paddy, and corn. One effort to reduce harvest loss, especially for dryland rice, is to implement good harvesting practices and technology, as well as good post-harvest handling and technology, thereby ensuring that low productivity can still guarantee stable food availability for the residents of Tubbi Taramanu Sub-district, especially in Pollewani Village. This community service activity was implemented through extension services, which included providing materials and facilitating interactive discussions. The counseling sessions were evaluated using questionnaires administered before and after the sessions. The evaluation results showed an increase in farmers' knowledge, as evidenced by the average participant score rising from 45.88 to 62.94.